Exploration of rituximab treatment strategies for membranous nephropathy adapted to the Chinese healthcare environment - Wang, Xiaolong; Cao, Xueying; Wu, Jie; Liang, Shuang; Yang, Jian; Wang, Hong (BMC nephrology, 2025)
This study aimed to explore the specific efficacy of rituximab (RTX) in the treatment of membranous nephropathy (MN) and compare and analyze the differences in effectiveness among various treatment regimens, with the objective of identifying the optimal treatment protocol suitable for the medical environment in China. This retrospective study focused on patients with MN who were treated with RTX and hospitalized at the First Medical Center of PLA General Hospital between January 1, 2019, and December 30, 2022. These patients were followed up for more than one year. We collected clinical data from these patients and categorized them into three groups on the basis of their RTX treatment background: the combined glucocorticoids (GCs) and/or immunosuppressants (IMS) and RTX monotherapy treatment groups, the initial and non-initial treatment groups, and the standard RTX and non-standard RTX treatment groups. The study evaluated the comprehensive outcomes of complete or partial remission during follow-up, as well as relapses after remission. Additionally, Cox regression analysis was conducted to identify risk factors influencing patient remission and relapse. A total of 126 patients were enrolled in this study, with an average age of 49.0 ± 13.4 years. Among them, males accounted for up to 77.8%, with an average BMI of 26.7 ± 4.0. Among these patients, 59.5% (75/126) received RTX combined with GCs and/or IMS. Statistical results revealed that the combined use of GCs and/or the IMS had no significant effect on renal remission (P = 0.439), but it accelerated the process of renal remission (P = 0.010). A total of 34.9% (42/126) of patients chose RTX as the initial treatment. Compared with the non-initial treatment group, this choice did not significantly differ in terms of efficacy or faster remission speed (all P > 0.05). On the other hand, 39.7% (50/126) of patients received the standard RTX treatment regimen. Compared with the non-standard group, the standard RTX treatment group presented a better remission rate (P < 0.001) and a faster remission speed (P = 0.027). During 13.0 (12.0, 20.0) months of follow-up, the cumulative remission rate reached 73% (92/126), including 47.6% (60/126) of patients with partial remission (PR) and 25.4% (32/126) of patients with complete remission (CR). The cumulative relapse rate was 20.7% (26/126). In addition, 17.5% (22/126) of patients experienced adverse reactions. Multivariate Cox regression analysis revealed that the standard RTX treatment regimen was associated with a better remission rate, whereas comorbid diabetes reduced the remission rate. Older age and higher white blood cell counts may lead to a higher relapse rate. This study revealed that RTX treatment has a high remission rate and a low relapse rate in MN patients. The standard RTX treatment regimen can provide better benefits. However, our experience is limited by its retrospective design and relatively small sample size, and further large-scale randomized controlled studies are needed to confirm our preliminary findings.